Development and Invitro Evaluation of Solid Lipid Nano Particles Loaded Topical Gel Containing Combination of Drugs Used In The Better Therapy of Psoriasis: Pharmaceutical Science-Lipid Nanoparticle for Better Psoriasis Therapy - Suryakumari Chalakanti; Narender Malothu (International Journal of Life Science and Pharma Research, 2022)
The present research work was aimed to develop a Solid lipid nanoparticles (SLNs) based topical gel for the treatment of psoriasis. SLNs were prepared and then incorporated in a topical gel as a carrier. High-Pressure Homogenization method was used to improved drug loading capacity and drug release properties. Excipients like Compritol 888 ATO, Tween 80,Precirol ATO5, Poloxamer407, Cremophor RH40, Carpobol 934, Methyl Paraben, TEA, Distilled water were used. The optimized formulations were based on Zeta potential, analysis of particle size, differential scanning Colorimetery, scanning electron microscopy and study of Invitro drug release. The present research study revealed that the SLNs based Gel containing F4 formulation could potentially exploit as a carrier with improved drug loading capacity and drug release properties. Thus, tacrolimus loaded SLNs formulation can be beneficial in the treatment of psoriasis. It was concluded that the prepared formulation can be used for treatment of psoriasis by using the topical therapy of nanogel and this will attempt to increase the efficacy of the drug at the site of action.